A high whey protein, vitamin D and E supplement preserves muscle mass, strength, and quality of life in sarcopenic older adults: A double-blind randomized controlled trial. Issue 1 (February 2019) - Bo, Yacong; Liu, Changfeng; Ji, Zhe; Yang, Ruihong; An, Qianqian; Zhang, Xueyuan; You, Jie; Duan, Dandan; Sun, Yafei; Zhu, Yiwei; Cui, Han; Lu, Quanjun
Summary: Objective: Sarcopenia, an age-related decline of muscle mass, strength, and physical function, was associated with falls, frailty, and poor quality of life. The aim of the current study is to examine the effect of nutritional supplement containing whey protein, vitamin D and E on measures of sarcopenia. Methods: A total of 60 sarcopenic older adult subjects participated in the current randomized, double-blind, placebo-controlled (iso-caloric control product) trial for 6 months. Muscle mass [Relative skeletal mass index (RSMI) measured by bioimpedance analysis (BIA)], muscle strength (handgrip strength), physical function (6-m gait speed, chair stand test, and timed-up-and-go test, TUG), quality of life (measured by Short-Form 36-Item Health Survey, SF-36), and blood biochemical indexes were measured before and after the 6-month intervention. Results: Compared to placebo group, nutritional supplementation improves RSMI (mean difference: 0.18 kg/m 2, 95% CI : 0.01–0.35, P = 0.040), handgrip strength (mean difference: 2.68 kg, 95% CI : 0.71–4.65, P = 0.009), SF-36 mental component summary (SF-36 MCS) (mean difference: 11.26, 95% CI : 3.86–18.65, P = 0.004), SF-36 physical component summary (SF-36 PCS) (mean difference: 20.21, 95% CI : 11.30–29.12, P < 0.001), serum IGF-1 (mean difference: 14.34 ng/mL, 95% CI : 2.06–26.73), IL-2 (mean difference: −575.32 pg/mL, 95% CI : −1116.94 ∼ −33.70, P = 0.038), serum vitamin D3 (mean difference: 11.01 ng/mL, 95% CI : 6.44–15, 58, P < 0.001), and serum vitamin E (mean difference: 4.17 ng/L, 95% CI : 1.89–6.45, P = 0.001). Conclusion: The current study demonstrated that the combined supplementation of whey protein, vitamin D and E can significantly improve RSMI, muscle strength, and anabolic markers such as IGF-I and IL-2 in older adults with sarcopenia. Further larger well-designed studies are warranted to evaluate whether long-term whey protein supplementation can blunt the declines of muscle function and mass in older adults with sarcopenia.